Composición y producción de tres canciones incorporando elementos del albazo ecuatoriano - Aguirre Aizaga, Génesis Nathalia (2022)
The present work of curricular integration has creative praxis as its central axis, as its objective is to carry out the composition and production of songs. In order to accomplish this task, it has been necessary to use the methodology of the qualitative approach, based on the non-experimental design. As a result, three songs were developed that incorporate melodic, harmonic, rhythmic and lyrical elements of the Ecuadorian albazo, deploying a musical discourse from the sound encounter between tradition and modernity in a contemporary and commercial popular music context, which concludes with the sound fixation of the creations in digital phonograms produced with the support of the research team of the project Creation, production and diffusion of musical work at the National University of Loja 2022-2023. Keywords: popular music, traditional Ecuadorian mestizo music, fusion, song composition.